2011
DOI: 10.2174/1874325001105010343
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Improvement in Quality of Life and Physical Activity After Total Knee Arthroplasty in Greek Elderly Women

Abstract: Background:The aim of this study was to evaluate the changes in quality of life of patients after total knee arthroplasty and to assess the changes in physical activity by using a self-reported questionnaire and by counting the number of steps 3-6 months after post-operatively.Methods:Included were fifty two elderly women (age 72.6±65.9 years, mean±SD) with knee osteoarthritis undergoing primary knee arthroplasty. Health-related quality of life, physical activity, pain and function and the number of steps were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 29 publications
(40 reference statements)
2
25
2
Order By: Relevance
“…The decline in PA in contrast to an increase in clinical outcome and well-being from presurgery status to 1 to 3 months after rehabilitation, followed by a further increase in PA, clinical outcome and well-being from 3 to 6 months after rehabilitation has been observed in previous studies [8, 13]. However, in our study the baseline PA values do not represent presurgery status.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…The decline in PA in contrast to an increase in clinical outcome and well-being from presurgery status to 1 to 3 months after rehabilitation, followed by a further increase in PA, clinical outcome and well-being from 3 to 6 months after rehabilitation has been observed in previous studies [8, 13]. However, in our study the baseline PA values do not represent presurgery status.…”
Section: Discussioncontrasting
confidence: 53%
“…However, the population investigated by Tsonga et al included several patients with contralateral pain and/or treatments, a higher BMI and less well-being 6 months after treatment, as demonstrated by an overall SF-36 score of 62.4 ± 2.7, a PCS of 56.7 ± 2.9 and a MCS of 68.1 ± 15.3 [8]. Knee and hip patients, investigated by Harding et al, showed statistically and clinically significant improvements in the Oxford Score and well-being 6 months postoperatively compared to the baseline values before surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desmeules et al [14] reported mean Physical Component Summary (PCS) and Mental Component Summary (MCS) scores from the SF-36 of 28 and 43, respectively, in 197 patients waiting for total knee arthroplasty (TKA); both of these values are well below the 25 th percentile compared to age- and gender-matched normative values [15]. Other studies have reported similarly low HRQoL in patients waiting for TKA [11, 16]. Notably, within a group of patients waiting for TKA who already report very low HRQoL, nearly 3 in 4 reported continued worsening in HRQoL during the mean 10-month waiting period before surgery [17].…”
Section: Hrqol In Knee Osteoarthritis Patientsmentioning
confidence: 99%
“…Although we could not found any differences in GCs/per day independence of age, patients in the other studies were about 10 years older in average [19, 20]. From the literature, we know that steps per day decrease with increasing age and physical activity decreases with age [12, 21].…”
Section: Discussionmentioning
confidence: 65%